Analysis of Forest Function Transfer to Oil Palm Plantation in Parenggean District with the Remote Sensing Approach and Geographic Information System - Marboles Kundrat; Frederik Samuel Papilaya (Politeknik Negeri Batam, 2019)
The island of Kalimantan is one of the islands that has a vast forest. Kalimantan Island is also the most important island for Indonesia, even the world. Parenggean is one of the sub-districts located in Kotawaringin Timur Regency, Central Kalimantan Province. Parenggean sub-district with an area of 493.15 km² is one of the sub-districts in East Kotawaringin Regency which has a very large oil palm plantation. This study will present data on the amount of forest land cover that has been converted. To get extensive forest conversion, this research uses the Remote Sensing and Geographic Information Systems approach. The result of research this proves there have been over the function forests became oil palm plantation in Parenggean District. The area of ​​forest that was converted into oil palm plantation in the research area is 5,143.15 hectares in 1990-2000 and 17,560.45 hectares in 2000-2010.